Association of Perinatal Factors With Severe Obesity and Dyslipidemia in Adulthood. (March 2022) - Tadese, Kristene; Ernst, Vivian; Weaver, Amy L.; Thacher, Tom D.; Rajjo, Tamim; Kumar, Seema; Kaufman, Tara; Wi, Chung-Il; Lynch, Brian A.
Background: Perinatal factors including gestational age, birthweight, size for gestational age, delivery route, maternal parity, maternal age, maternal education, socioeconomic status, race, and sex, are associated with the future risk of obesity and co-morbid conditions. This study evaluated the relationship of birthweight for gestational age and perinatal factors with severe obesity and dyslipidemia in adulthood. Methods: We conducted a population-based, retrospective birth cohort study of infants born to residents of Olmsted County, MN between 1976 and 1982. Outcomes were assessed after age 18 years until October 2020, including severe obesity (BMI ≥ 40 kg/m 2 ) and dyslipidemia (total cholesterol ≥200 mg/dL, non-high density lipoprotein [non-HDL] cholesterol ≥145 mg/dL or HDL cholesterol <40 mg/dL). We obtained mother's age, education level, and parity as well as newborn sex, race, type of delivery, single/multiple birth, gestational age, and birthweight from birth certificate data. Individual-level socioeconomic status (SES) of the household at birth was determined with the HOUSES index. Results: Of 10 938 birth cohort subjects, 7394 had clinic visits after age 18 years and were included, with 2630 having severe obesity (n = 798) or dyslipidemia (n = 2357) as adults. In multivariable models, female sex, singleton birth, less maternal education, and lower SES defined by HOUSES were independently associated with an increased risk of severe obesity in adulthood. Non-white race, singleton birth, and lower birthweight were independently associated with adult dyslipidemia. Birthweight for gestational age was not associated with severe obesity or dyslipidemia. Conclusion: Perinatal factors were associated with both severe obesity and dyslipidemia in adulthood. Lower SES at birth was predictive of severe obesity in adulthood, highlighting the opportunity to investigate modifiable perinatal social determinants to reduce the risk of severe obesity.